Covalent Immobilization of EPCs-Affinity Peptide on Poly(L-Lactide-co-epsilon-Caprolactone) Copolymers to Enhance EPCs Adhesion and Retention for Tissue Engineering Applications - Rhee, Jongyoon; Shafiq, Muhammad; Kim, Donghak; Jung, Youngmee; Kim, Soo Hyun (한국고분자학회, 2019)
Small diameter vascular grafts (inner diameter 6 mm) have a critical limitation regarding inner thrombotic reaction and occlude when implanted as artificial substitutes. In situ capture of endothelial progenitor cells (EPCs) could be beneficial to improve the endothelialization of artificial blood vessels. This study aimed to develop EPCs-affinity peptide (TPSLEQRTVYAK, TPS) and heparin-conjugated star-shaped poly(L-lactide-co-epsilon-caprolactone) (St-PLCL) copolymers to simultaneously capture EPCs and improve the hemocompatibility of vascular grafts, respectively. Electrospun membranes and small-diameter vascular grafts were fabricated by mixing linear PLCL, heparin-conjugated St-PLCL (PLCL-Hep), and TPS-conjugated St-PLCL (PLCL-TPS) copolymers. Vascular grafts exhibited biomechanical properties similar to the ISO standard. Membranes containing PLCL-Hep and PLCL-TPS showed fewer adhered platelets than did the control membranes. Moreover, electrospun membranes containing PLCL-Hep and PLCL-TPS adhered significantly to more EPCs than did the control group; however, three types of membranes did not appreciably differ in terms of the attachment of endothelial cells (ECs). Subcutaneous implantation of vascular grafts in Sprague-Dawley rats led to cellular infiltration and neotissue formation, which increased with the passage of time. Taken together, PLCL-TPS and PLCL-Hep copolymers can be fabricated into small-diameter vascular grafts to facilitate endothelialization through endogenous cell recruitment for vascular tissue regeneration applications.